Archie & Friends #136 - Ruiz, Fernando (Archie Comics, 2011)
It's a kitchen catastrophe when Ms. Beazly is temporarily sidelined by an injury, but never fear - Ms. Beazly's culinary school grad daughter, Bella, is here! All the guys go ga-ga over the chic chef, but will the food she serves be as attractive? Can Jughead simultaneously feel love in his heart and hunger in his stomach?